Dimensions of debt in selected economies: Analysis on determinants, thresholds and effects on economy / Chandran Gunalan - Chandran , Gunalan (2021)
This research examines three dimensions of public debt among a group of 12 uppermiddle Asian countries, as well as country-specific analysis on China, Indonesia, Malaysia, Thailand and Turkey. An ARDL model was used to analyse the determinants of public debt, while Threshold Regression was applied to estimate the threshold level and understand the impact of breaching the threshold using panel data between 1980 and 2015. Firstly, the determinants of public debt indicate that GDP growth, capital stock, national saving, total trade, and inflation are factors that reduce the level of public debt. However, employment, government consumption, real interest rate and real exchange rate increase public debt levels. Crisis periods are also times when countries are exposed to public debt, but the results show such an effect only among country specific analyses. Secondly, public debt threshold (turning point) was estimated involving 12 upper middleincome economies from Asia. Results show that there is a non-linear relationship between public debt and economic growth in the long-run and this relationship exists in both Ushape and inverted U-shape (Ո). Public debt threshold is estimated at 96.9% for 12 upper